2016
DOI: 10.2144/000114436
|View full text |Cite
|
Sign up to set email alerts
|

Parallelized Cytoindentation Using Convex Micropatterned Surfaces

Abstract: Here we present a high-throughput, parallelized cytoindentor for local compression of live cells. The cytoindentor uses convex lens-induced confinement (CLiC) to indent micrometer-sized areas in single cells and/or populations of cells with submicron precision. This is accomplished using micropatterned poly(dimethylsiloxane) (PDMS) films that are adhered to a convex lens to create arrays of extrusions referred to here as "posts." These posts caused local deformation of subcellular regions without any evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Each type has its own advantages and disadvantages. Cell indentation with a flat end tip is also known as cytoindentation [27]. Normally, the size of indentation tip is smaller than the cell.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Each type has its own advantages and disadvantages. Cell indentation with a flat end tip is also known as cytoindentation [27]. Normally, the size of indentation tip is smaller than the cell.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…This technique had been shown to be able to successfully confine and isolate diffusing [5] and interacting molecules [10][11][12] for long periods and improve fluorescent signal detection [7]. To date, CLiC has primarily been used to study materials, biomolecules and particles, with only limited information available regarding its suitability for live-cell investigations [13].…”
Section: Graphical Abstract Methods Summarymentioning
confidence: 99%
“…This device also holds great potential for routine use in fields such as cancer research, where single-cell variabilities and instabilities are especially important for developing effective therapies. While we focused on yeast cells as a model system in this work, previous studies performed on adherent Chinese hamster ovary (CHO-K1) cells demonstrated the feasibility of customizing the CLiC instrument with a cytoindentor, which allows precise indentation and imaging of live mammalian cells without significantly changing their oxidative stress or causing detectable impacts on cell fitness [13]. To manipulate cell adherence, the flow cells could be customized and coated with fibronectin as previously demonstrated [13].…”
Section: Yeast Cell Growth Study In Flow Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for the precision of the point cloud data processing is getting higher and higher, and the point cloud data processing technology is developing continuously [4]. In the process of measurement, because there are no obvious geometric distribution in most cases and no obvious topological structure between data points with no organizational order, the whole point cloud presents a state of scattered and irregularities [5]. The reconstruction of the scattered point cloud data has become the key subject for researchers [6].…”
Section: Introduction *mentioning
confidence: 99%